Quality of life among patients after Hodgkin lymphoma treatment: a 3-year prospective study - B. B. Samura (Zaporozhye State Medical University, 2017)
The purpose of the study was to investigate the quality of life among patients after Hodgkin lymphoma treatment to estimate demographic, clinical, psychosocial risk factors of unfavorable prognosis depending on the occurrence of cardiovascular events. Materials and methods. Population sample was 38 patients after Hodgkin lymphoma treatment. All patients received the interviewer, 35 patients (92.1% of all respondents) answered the questions and were included to the study. Clinical visits have been conducted each month for 3 years after enrollment, during which cardiovascular events have been recorded. Results: During observation period progression of Hodgkin lymphoma was proved in 8 patients, 3 persons were excluded for poor follow-up. Thirty four cumulative clinical events occurred in 12 patients (50%) within the follow-up, with their distribution being as follows: 2 cardiovascular deaths, 16 cardiac arrhythmias, 6 cardiac ischemic events, 1 stroke, 4 chronic heart failures and 5 hospital admissions for cardiovascular reasons. 3 deaths were not related with cardiovascular pathology or cardiovascular reasons. 3 deaths were not related with cardiovascular pathology. Patients who had cardiovascular events reported significantly worse physical functioning after anthracyclines with cumulative dose ≥326 mg/m2, after mediastinal radiotherapy. There were significant lower level of vitality in patients with cardiovascular events (p<0.001), in patients with advanced stages and mediastinal radiotherapy. After second-line treatment (MINE) patients had much worse physical functioning (p<0.001) that was associated with quality of life outcomes. There were significant differences in mental health, (р<0.001), role-psychological (р<0.03) scales. The lower level of mental health was associated with disease stages, doses of radiotherapy. Conclusion: The general health perceptions and vitality levels of Hodgkin lymphoma survivors depends on passed courses of chemotherapy, appearance of cardiovascular events during 3 years.